Camera surveillance: An analysis of preventive rationalities and panopticism in relation to an expanding technology of social control. - Weston, Dean R. (University of Ottawa (Canada), 2000)
At present, we are increasingly both the object of surveillance and the observers of images gathered through various surveillance practices. Although camera surveillance is a situational crime prevention (SCP) practice that is expected to deter criminal incidents and victimization, there is the potential for these panoptic technologies to produce more widespread and subtle social control effects. Contemporary liberal-based governments have constructed new modes of governance that delegate responsibility for risk-management to their populaces in specific ways. The use of camera surveillance is an extension of such a mode of governance that encourages individuals to identify with and adopt the preventive rationalities that underlie the use of these technologies. Consequently, camera surveillance practices have the potential to encourage individuals to monitor their own thinking and conduct and govern themselves in accordance to what is deemed to be appropriate behaviours. This thesis undertakes to explore the potential social control effects of current camera surveillance practices.
Keywords: Psychology, Social.